Respuestas

2012-05-02T03:43:32+02:00

f(x)=2x+1

f(1)=2(1)+1=3

f(-2)=2(-2)+1=-3

f(1/2)=2(1/2)+1=2

f(raiz de 5)=2(rais de 5)+ 1

f(a)=2a+1

f(-a)=-2a+1

f(a+b)=2a+2b+1

2012-05-02T03:47:24+02:00

si dice f(1), tenes que poner 1 en donde aparece la x...

f(1)= 2*1+1=2+1=3

si dice f(-2) pone -2 en lugar de la x...

f(-2)= 2*(-2)+1=-4+1=-3

y sai con cada uno...

f(1/2)=2*(1/2)+1=1+1=2

f(raiez de 5)=2*raiiz de 5+1=2*2.23+1=4.46+1=5.46

f(a)=2(a)+1=2a+1

f(-a)=2(-a)+1=-2a+1

f(a+b)=2(a+b)+1=2a+2b+1